2015
DOI: 10.1002/pros.23043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of autoimmune inflammation induced prostate stem cell expansion

Abstract: Background The presence of inflammation in prostate cancer (PCa) and benign prostate hyperplasia (BPH) has been well described but the cellular mechanisms by which inflammation modulates the prostate are currently unclear. Prostate stem cells (PSC) not only maintain prostate homeostasis but also are considered to be the cell of origin of PCa and an important contributor to BPH. However, the impact of inflammation on PSC is not well understood. Therefore, we initiated studies to evaluate the effect of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Importantly, chronic inflammation induced by bacterial models in non‐genetically modified mice are not fully penetrant, do not affect all lobes, and have not yet been fully characterized and quantified. Genetically engineered mice such as the POET‐3 autoimmune mouse model require particular background strains and back‐breeding of protein knockouts onto the genetic strain of inflammation, which is costly and time consuming . Additionally, hormone models yield many off‐target and systemic effects making data interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, chronic inflammation induced by bacterial models in non‐genetically modified mice are not fully penetrant, do not affect all lobes, and have not yet been fully characterized and quantified. Genetically engineered mice such as the POET‐3 autoimmune mouse model require particular background strains and back‐breeding of protein knockouts onto the genetic strain of inflammation, which is costly and time consuming . Additionally, hormone models yield many off‐target and systemic effects making data interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hormone models yield many off‐target and systemic effects making data interpretation difficult. Finally, each of the models produce variable responses …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal protocols used in this study were approved by Purdue Animal Care and Use Committee. The prostate stem cell population was isolated as previously described . Briefly, minced prostate tissue from 8 to 12 week‐old mice was digested with 1 mg/mL Collagenase‐I (Sigma‐Aldrich) in RPMI 1640 medium with 10% FBS for 2 hours, followed by trypsinization at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in mouse models have demonstrated that acute inflammation promotes an expansion of progenitor-like cells, 8 and an increase in basal-to-luminal differentiation. 9 While we show that PIA-like luminal cells are enriched in regions of inflammation, an inability to study kinetic processes in human tissue prevents us from uncovering the sequence of events that links inflammation and PIA-like luminal progenitor cells.…”
mentioning
confidence: 97%